Parada cardíaca inesperada durante colecistectomia. Relato de caso - Da Justa Croitor, Lorena Brito [UNESP]; Pinheiro Módolo, Norma Sueli [UNESP]; Cerqueira Braz, José Reinaldo [UNESP]; Rojas, Alfredo Cury [UNESP] (My University, 2002)
Background and Objectives - Intraoperative cardiac arrest is a severe event and its incidence in our hospital is 31:10000 anesthesias. This report aimed at presenting a case of cardiac arrest during general anesthesia in a patient submitted to chotecystectomy. Case Report - Female patient. 16 years old. 62 kg, physical status ASA I, submitted to chotecystectomy. Patient was premedicated with 15 mg midazotam. Anesthesia was induced with sufentanil (50 μg), propofol (150 mg) and atracurium (30 mg), and was maintained with isoflurane and nitrous oxide. After thirty minutes of surgery, there was an episode of sinus bradycardia reverted with atropine (0.5 mg). Twenty minutes later, there was another episode of bradycardia with a third-degree atrio-ventricular block, rapidly progressing to cardiac arrest in asystole despite the administration of atropine (1 mg). Resuscitation maneuvers were immediately started, simultaneously with the administration of epinephrine (1 mg) and spontaneous cardiac activity returned in approximately 5 minutes. Surgery was concluded and patient remained hemodynamically stable. Patient was extubated two hours after surgery, somnolent, with satisfactory respiratory pattern and hemodynamic stability. After 12 hours of clinical observation at the Intensive Care Unit, patient was agitated and confused. Patient was discharged from the ICU twenty-four hours after cardiac arrest, conscious, oriented, without complaints or neurological deficits. Patient was discharged in the 4 thpostoperative day. Conclusions - Many conditions may contribute to perioperative arrhythmias and cardiac arrest, including vagal stimulation secondary to surgical maneuvers. Early diagnosis and immediate resuscitation maneuvers are critical for a good neurological outcome.
Unexpected cardiac arrest during cholecystectomy. Case report
Keywords: Complications: cardiac arrest; SURGERY. General: videolaparoscopy